31.3k views
0 votes
Simplify 4.2(2x-0.5y)-2(4.1x-0.3y)

User KeenUser
by
5.1k points

2 Answers

3 votes

Answer:

x = 7.5y

Explanation:

Simplifying

4.2(2x + -0.5y) + -2(4.1x + -0.3y) = 0

(2x * 4.2 + -0.5y * 4.2) + -2(4.1x + -0.3y) = 0

(8.4x + -2.1y) + -2(4.1x + -0.3y) = 0

8.4x + -2.1y + (4.1x * -2 + -0.3y * -2) = 0

8.4x + -2.1y + (-8.2x + 0.6y) = 0

Reorder the terms:

8.4x + -8.2x + -2.1y + 0.6y = 0

Combine like terms: 8.4x + -8.2x = 0.2x

0.2x + -2.1y + 0.6y = 0

Combine like terms: -2.1y + 0.6y = -1.5y

0.2x + -1.5y = 0

Solving

0.2x + -1.5y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1.5y' to each side of the equation.

0.2x + -1.5y + 1.5y = 0 + 1.5y

Combine like terms: -1.5y + 1.5y = 0.0

0.2x + 0.0 = 0 + 1.5y

0.2x = 0 + 1.5y

Remove the zero:

0.2x = 1.5y

Divide each side by '0.2'.

x = 7.5y

Simplifying

x = 7.5y

User Sarcastyx
by
5.3k points
3 votes

Answer:

0.2 - 1.5

Explanation:

have a great day!! :)

User Russell Davis
by
4.5k points